Voluntary is better than involuntary cough peak flow for predicting re-intubation after scheduled extubation in cooperative subjects - Duan, Jun; Liu, Jinhua; Xiao, Meiling; Yang, Xiangmei; Wu, Jinxing; Zhou, Lintong (Respiratory care, 2014)
In this study, we compared the predictive accuracy of voluntary cough peak flow (V-CPF) and involuntary cough peak flow (IV-CPF) for re-intubation in mechanically ventilated subjects. Endotracheally intubated patients who passed a spontaneous breathing trial and assessment of readiness for extubation were enrolled. Before extubation, V-CPF and IV-CPF were measured. Re-intubation was recorded at 72 h after extubation. A total of 115 extubations in 106 cooperative subjects (including 9 subjects with second extubation) and 5 extubations in 5 uncooperative subjects were recorded. At 72 h, 20 (17.4%) and 1 (25%) instances of re-intubation occurred in cooperative and uncooperative subjects, respectively. In cooperative subjects, those who had been successfully extubated had higher V-CPF than re-intubated subjects (81.3 ± 41.4 vs 51.3 ± 31.7, P = .003). However, rates were not significantly different with IV-CPF (70.9 ± 39.8 vs 55.7 ± 37.9, P = .121). Areas under the curve of the receiver operating characteristic in V-CPF and IV-CPF were 0.743 ± 0.057 and 0.632 ± 0.069 (P < .001 and P = .058, respectively, compared with area under the curve = 0.5). V-CPF had higher predictive accuracy for re-intubation than IV-CPF (P = .034). In subjects with a lower quartile and third quartile V-CPF (≤ 43.2 L/min and 43.2-68.4 L/min, respectively), V-CPF was similar to IV-CPF. However, in second quartile and upper quartile V-CPF (68.4-99.0 L/min and > 99.0 L/min, respectively), V-CPF was higher than IV-CPF (82.1 ± 9.6 vs 66.6 ± 19.5 L/min, P < .001; 135.5 ± 29.8 vs 116.2 ± 38.2 L/min, P = .006, respectively). Overall, V-CPF was higher than IV-CPF (76.0 ± 41.4 vs 68.2 ± 39.7, P = .003). In uncooperative subjects, the IV-CPF was higher than V-CPF (40.2 ± 10.2 vs 79.2 ± 29.0, P = .042). V-CPF is noninvasive. It is much more accurate than IV-CPF as a predictor of re-intubation in cooperative patients because the IV-CPF may underestimate cough strength in patients with high V-CPF. However, it is unclear which is optimal for use in uncooperative patients.